Risk Factors for Thyroid Cancer: A Hospital-Based Case-Control Study in Korean Adults - Myung, Seung-Kwon (Cancer Res Treat, 2017)
PURPOSE: Although the incidence of thyroid cancer in Korea has rapidly increased over the past decade, few studies have investigated its risk factors. This study examined the risk factors for thyroid cancer in Korean adults. MATERIALS AND METHODS: The study design was a hospital-based case-control study. Between August 2002 and December 2011, a total of 802 thyroid cancer cases out of 34,211 patients screened from the Cancer Screenee. Cohort of the National Cancer Center in South Korea were included in the analysis. A total of 802 control cases were selected from the same cohort, and matched individually (1:1) by age (±2 years) and area of residence for control group 1 and additionally by sex for control group 2. RESULTS: Multivariate conditional logistic regression analysis using the control group 1 showed that females and those with a family history of thyroid cancer had an increased risk of thyroid cancer, whereas ever-smokers and those with a higher monthly household income had a decreased risk of thyroid cancer. On the other hand, the analysis using control group 2 showed that a family history of cancer and alcohol consumption were associated with a decreased risk of thyroid cancer, whereas higher body mass index (BMI) and family history of thyroid cancer were associated with an increased risk of thyroid cancer. CONCLUSION: These findings suggest that females, those with a family history of thyroid cancer, those with a higher BMI, non-smokers, non-drinkers, and those with a lower monthly household income have an increased risk of developing thyroid cancer.